EVALUATION OF ANTIMICROBIAL AND SYNERGISTIC ANTIMICROBIAL PROPERTIES OF PTEROCARPUS SANTALINUS - Donga, Savan; Moteriya, Pooja; Chanda, Sumitra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The aim of the present study was to evaluate antibacterial and synergistic antimicrobial properties of leaf, stem and bark of Pterocarpus santalinus. Methods: The extraction was done by decoction method. The antimicrobial activity was done by agar well diffusion assay and the synergistic antimicrobial activity was done by agar disc diffusion assay. Results: The synergistic activity was studied with plant extracts plus antibiotics viz. Ampicillin , Polymyxin-B, Clotrimazole and Fluconazole. Conclusions: Amongst the three parts, the best antimicrobial activity was shown by bark extract. All the three parts showed synergistic antimicrobial activity with antibiotics but their level varied. The results suggest that all the three parts phytochemicals that enhance the antimicrobial efficacy of the antibiotics against some microorganisms and hence can be developed as a new therapeutic weapon against infectious diseases.